TREGking From Gut to Brain: The Control of Regulatory T Cells Along the Gut-Brain Axis - Choi, Juli; Kim, Bo-Ram; Akuzum, Begum; Chang, Leechung; Lee, June-Yong; Kwon, Ho-Keun (Frontiers in Immunology, 2022)
The human gastrointestinal tract has an enormous and diverse microbial community, termed microbiota, that is necessary for the development of the immune system and tissue homeostasis. In contrast, microbial dysbiosis is associated with various inflammatory and autoimmune diseases as well as neurological disorders in humans by affecting not only the immune system in the gastrointestinal tract but also other distal organs. FOXP3+ regulatory T cells (Tregs) are a subset of CD4+ helper T cell lineages that function as a gatekeeper for immune activation and are essential for peripheral autoimmunity prevention. Tregs are crucial to the maintenance of immunological homeostasis and tolerance at barrier regions. Tregs reside in both lymphoid and non-lymphoid tissues, and tissue-resident Tregs have unique tissue-specific phenotype and distinct function. The gut microbiota has an impact on Tregs development, accumulation, and function in periphery. Tregs, in turn, modulate antigen-specific responses aimed towards gut microbes, which supports the host–microbiota symbiotic interaction in the gut. Recent studies have indicated that Tregs interact with a variety of resident cells in central nervous system (CNS) to limit the progression of neurological illnesses such as ischemic stroke, Alzheimer's disease, and Parkinson's disease. The gastrointestinal tract and CNS are functionally connected, and current findings provide insights that Tregs function along the gut-brain axis by interacting with immune, epithelial, and neuronal cells. The purpose of this study is to explain our current knowledge of the biological role of tissue-resident Tregs, as well as the interaction along the gut-brain axis.